Perancangan Prototipe Aplikasi Transportasi Umum Jabodetabek Berbasis Mobile dengan Pendekatan User-Centered Design - Cahaya Arzeti; Pudy Prima; Reza Maulana (LPPM STT Terpadu Nurul Fikri, 2026)
The problem of congestion and low public interest in public transportation in Jabodetabek is caused by the lack of integration between modes, as well as limited access to information and payment systems. This research aims to design the user interface (UI) and user experience (UX) of a mobile application that integrates various modes of public transportation using the User-Centered Design (UCD) approach. Data was collected through surveys, interviews, and observations. The prototype was designed in Figma and tested in Maze using the System Usability Scale (SUS) method. The evaluation results showed an average SUS score of 82.7, which indicates a good level of usability. This research resulted in an intuitive application prototype that supports a more efficient user experience and contributes to the design of public transportation systems based on user needs. The findings are expected to encourage increased adoption of public transportation in Jabodetabek.